The assessment of potential passenger transportation through east Zangezur-Nakhchıvan tourism route - Jabbarova, Leyla (Azərbaycan Texniki Universiteti, 2023)
The rapidly changing modern world economy and increasing global competition require companies to apply new approaches and technologies in management and supply issues. The increase in the price of limited resources, especially energy and raw materials, the new geopolitical situation on a global and regional scale, as well as the rapid application of technological innovations in the economy bring global trends such as economic efficiency, speed and longevity to the fore.